Conceptualiztion of the evolution of approaches to the public administration digitalization under crisis-driven transformation - Viacheslav Laptiev; Olga Ivanova; Andrii Protsenko (Technology audit and production reserves, 2026)
The object of research is the process of public administration digitalization under conditions of crisis transformations and institutional instability. The problem that was solved is the lack of clarity regarding the interaction between platform governance, sustainable governance, and crisis-driven digital transformation. That happened due to the impact of global crisis-driven transformations, the accelerated development of digital technologies, and the changing role of the state in the digital society. It explores the evolution of approaches to the digitalization of public administration through a combination of theoretical and bibliometric analysis. It examines the transformation of digital governance paradigms from e-governance to platform governance, sustainable governance, and ecosystem-based governance. The methodological basis is a bibliometric analysis of scientific works indexed in the Scopus database 1992–2026, using VOSviewer. Analysis of the co-occurrence of keywords revealed dominant thematic clusters, conceptual shifts, and stages of development of digital governance research. The research results indicate that the evolution of digital governance is nonlinear and cumulative in nature. New paradigms do not displace previous ones, but integrate them into more complex governance models. An increase in scientific interest in the issues of digital governance transformation has been observed after the COVID-19 and global crisis transformations of 2020–2025. Special attention is paid to the Ukrainian context of digital transformation. The concept of compressed digital governance as a crisis-oriented model of accelerated and overlapping digital transformation in conditions of war, institutional instability and resource constraints is substantiated. It is argued, Ukraine is a unique case where elements of e-government, platform governance and sustainable governance are implemented at the same time. The resulting conceptualization of the evolution of approaches to public administration can be used to form public policy strategies aimed at digital transformation and state sustainability.